2022
DOI: 10.1093/cid/ciab1066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Mucorales Polymerase Chain Reaction (PCR) for the Diagnosis of Mucormycoses: The MODIMUCOR Prospective Trial

Abstract: Background Early diagnosis and prompt initiation of specific antifungal treatment is essential for improving the prognosis of mucormycosis. We aimed to assess the performance of serum Mucorales quantitative PCR (qPCR) for the early diagnosis and follow-up of mucormycosis. Methods We prospectively enrolled 232 patients with suspicion of invasive mold disease, evaluated using standard imaging and mycological procedures. Thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…In addition, our study was grossly underpowered to evaluate whether there are differences among Mucorales in terms of culture positivity from infected lung tissues. Interestingly, a recent study indicated that some Mucorales, such as Rhizimucor species, do not grow well in clinical samples and are better diagnosed by PCR [11]. Lastly, nearly all patients in this study had cytopenia with significant cumulative immune suppression due to their underlying conditions.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, our study was grossly underpowered to evaluate whether there are differences among Mucorales in terms of culture positivity from infected lung tissues. Interestingly, a recent study indicated that some Mucorales, such as Rhizimucor species, do not grow well in clinical samples and are better diagnosed by PCR [11]. Lastly, nearly all patients in this study had cytopenia with significant cumulative immune suppression due to their underlying conditions.…”
Section: Discussionmentioning
confidence: 67%
“…Once the diagnosis is made, quantitative PCR (qPCR) may be used within seven days after treatment initiation to monitor the response to liposomal-amphotericin B. A negative qPCR after seven days of treatment is associated with an 85% lower 30-day mortality rate [37]. Pulmonary findings might be similar to pulmonary aspergillosis, with infiltration, consolidation, nodules, cavitations, atelectasis, effusion, posterior band thickening, hilar or mediastinal adenopathy, or normal appearance [5].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a French prospective multicenter study (the MODIMUCOR study) which evaluates a Mucorales quantitative PCR in serum for the diagnosis of invasive mucormycosis has been published [ 21 ]. There were 245 patients divided into two cohorts.…”
Section: Advances In Molecular Diagnosismentioning
confidence: 99%